Daily plan-do-check-act (PDCA) cycles with level of development (LOD) 400 objects for foremen. (April 2020) - Song, Min Ho; Fischer, Martin
Highlights: Quantitative approach to a daily plan-do-check-act (PDCA) cycle is challenging. An ontology that addresses this problem for a foreman is proposed. The ontology uses LOD400 objects and imaginary boundaries for quantitative approach. A software prototype is developed based on the ontology. Foremen tested the prototype and went through daily PDCA cycles with LOD400 objects. Abstract: Level of development (LOD) 400 objects have the required information for definitively defining a list of materials and their quantities for a certain scope of construction work. Generating this information each day and operating LOD400 objects through the plan-do-check-act (PDCA) cycle on a daily basis could provide the quantitative basis for proactive and precise day-to-day field control. However, the high frequency of the cycle and the granularity of LOD400 make the process time-consuming and onerous for a foreman. The contribution of this research is an ontology that enables a foreman to go through the PDCA cycle on a daily basis with LOD400 objects and generate six information items (actual date of work completed, products built, location of products built, quantities of materials installed, number of workers that were on site, and performance metric) after the check step C of the PDCA cycle. The ontology was developed into a software prototype for field experiments and the results show that foremen can go through the daily PDCA cycle with LOD400 objects in 2 min and 47 s on average. The average usability score of the prototype was 95, which falls between "excellent" and "best imaginable" on the System Usability Scale (SUS).